A review of processing technologies for vanadium extraction from stone coal. Issue 3 (1st October 2020) - Wang, Mingyu; Huang, Sheng; Chen, Bianfang; Wang, Xuewen
ABSTRACT: Due to the poor vanadium recovery of mineral processing, the extraction of vanadium from stone coal is directly carried out by metallurgical processes. Salt process, acid process and alkali process three types of stone coal leaching including nine technologies are introduced. However, all of these nine leaching technologies have serious disadvantages and up to now the stone coal has not been efficiently utilised. Chemical precipitation, ion exchange and solvent extraction all can be used to extract vanadium from stone coal leach solutions. Due to the low extraction of vanadium, Chemical precipitation method is rarely used. Ion exchange is only used for the extracting of V(V) from the leach solution. For the extraction of low valence, P204 is one of effective extraction agent. The lately developed technology, LTSRWL, is characterised by high recovery of vanadium, comprehensive recovery of other valuable elements and environmental friendliness, which make it become the best option.